2017
DOI: 10.3391/mbi.2017.8.4.05
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Asian clams (Corbicula fluminea) recorded from 2001 to 2016 in Massachusetts, USA

Abstract: Experimental studies evaluating the effects of food availability on the movement of free-ranging animals generally involve food supplementation rather than suppression. Both approaches can yield similar insights, but we were interested in the potential for using food suppression for the management and control of invasive predators, in particular, the brown treesnake (Boiga irregularis) on Guam. However, understanding a species' response to food resources is critical before employing such a strategy. We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Accordingly, a mosaic of freshwater environments are susceptible to the introduction and establishment of these invasive bivalves, which can subsequently act as new source locations that facilitate further spread (Sousa et al 2014 ; Karatayev et al 2015 ). Therefore, there remains an urgent need to develop and validate a suite of tools for rapid population control and eradication of emerging and existing populations (Colwell et al 2017 ; Coughlan et al 2018b , 2019b ). To date, although extensive population-control experiments have been conducted on both C. fluminea (Wittmann et al 2012a , b ; Sheehan et al 2014 ) and D. polymorpha (Luoma et al 2018 ), none of them have been successful in providing substantial long-term management of these invaders.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a mosaic of freshwater environments are susceptible to the introduction and establishment of these invasive bivalves, which can subsequently act as new source locations that facilitate further spread (Sousa et al 2014 ; Karatayev et al 2015 ). Therefore, there remains an urgent need to develop and validate a suite of tools for rapid population control and eradication of emerging and existing populations (Colwell et al 2017 ; Coughlan et al 2018b , 2019b ). To date, although extensive population-control experiments have been conducted on both C. fluminea (Wittmann et al 2012a , b ; Sheehan et al 2014 ) and D. polymorpha (Luoma et al 2018 ), none of them have been successful in providing substantial long-term management of these invaders.…”
Section: Introductionmentioning
confidence: 99%
“…Chase et al (2017) mentioned that, this clams preferred a habitat with fine or coarse sand substrates rather than mud or bare concrete. Colwell et al (2017) also found that substrates influence the distribution of this clam. C. fluminea grow up with the ability to efficiently meet their metabolic needs by collecting food from their substrates (Noreña et al, 2015).…”
Section: Substrates Compositionmentioning
confidence: 72%
“…One of plants of the family, Ceratophyllaceae, it is considered one of the important aquatic plants, which is classified among the submerged aquatic plants [1]. There are four species of the genus Ceratophyllum , but the most prevalent is the type Ceratophyllum demersum, and spread in Asian regions such as China, Japan, Iraq, Egypt and Vietnam, as for the rest of the species, they are found in the United States of America, such as the type C. echinatum, and it is found in northwest America, while the type C. maricatum spreads in large areas in the states of Florida and northern California [2,3,4].…”
Section: Introductionmentioning
confidence: 99%